Privacy in Social Media - Hirawan, Jeffry; Rasyid, Itmam Al (Journal of Applied Information, Communication and Technology, 2020)
Nowadays social networks become very common. People use social media to keep people in touch, businesses, organizations, and many more. The information you share with your friends in the social media allows them easily to keep in touch with you. However beside friends, colleges, relatives, there are many people that are interested in the private information on social media. Identity thieves, scam artists, debt collectors, stalkers, companies use social networks to gather information. Companies that use social networks for getting information about people are intended to personalize their services for the users and to sell to advertisement. In this paper we will discuss the advantage and disadvantage of using social media and what kind of information is safe to post and how to protect it.